NRF-2/HO-1 Pathway-Mediated SHOX2 Activation Is a Key Switch for Heart Rate Acceleration by Yixin-Fumai Granules. (26th September 2022) - Zhang, Heng; Chen, Chen; Liu, Yue; Ren, Lu; Qi, Jing; Yang, Yang; Chen, Wei; Yao, Yingjia; Cai, Xintong; Liu, Zhuang; Hao, Miao; Li, Lingkang; et al.
Abstract : Population aging has led to increased sick sinus syndrome (SSS) incidence; however, no effective and safe medical therapy has been reported thus far. Yixin-Fumai granules (YXFMs), a Chinese medicine granule designed for bradyarrhythmia treatment, can effectively increase SSS patients' heart rate. Senescence-induced sinoatrial node (SAN) degeneration is an important part of SSS pathogenesis, and older people often show high levels of oxidative stress; reactive oxygen species (ROS) accumulation in the SAN causes abnormal SAN pacing or conduction functions. The current study observed the protective effects of YXFMs on senescent SAN and explored the relationship between the NRF-2/HO-1 pathway, SHOX2, and T-type calcium channels. We selected naturally senescent C57BL/6 mice with bradycardia to simulate SSS; electrocardiography, Masson's trichrome staining, and DHE staining were used to assess SAN function and tissue damage. Immunofluorescence staining and Western blotting were used to assay related proteins. In vitro, we treated human-induced pluripotent stem cell-derived atrial myocytes (hiPSC-AMs) and mouse atrial myocyte-derived cell line HL-1 with D-galactose to simulate senescent SAN-pacemaker cells. CardioExcyte96 was used to evaluate the pulsatile function of the hiPSC-AMs, and the mechanism was verified by DCFH-DA, immunofluorescence staining, RT-qPCR, and Western blotting. The results demonstrated that YXFMs effectively inhibited senescence-induced SAN hypofunction, and this effect possibly originated from scavenging of ROS and promotion of NRF-2, SHOX2, and T-type calcium channel expression. In vitro experiment results indicated that ML385, si- SHOX2, LDN193189, and Mibefradil reversed YXFMs' effects. Moreover, we, for the first time, found that ROS accumulation may hinder SHOX2 expression; YXFMs can activate SHOX2 through the NRF-2/HO-1 pathway-mediated ROS scavenging and then regulate CACNA1G through the SHOX2/BMP4/GATA4/NKX2-5 axis, improve T-type calcium channel function, and ameliorate the SAN dysfunction. Finally, through network pharmacology and molecular docking, we screened for the most stable YXFMs compound that docks to NRF-2, laying the foundation for future studies.